ME 03-2 HIGH SALT INTAKE AS A CAUSE OF OBESITY. (September 2016) - MacGregor, Graham
Abstract : High salt intake is the major cause of raised blood pressure and accordingly leads to cardiovascular diseases. Recently, it has been shown that high salt intake is associated with an increased risk of obesity through sugar-sweetened beverage consumption. Increasing evidence also suggests a direct link. Our study aimed to determine whether there was a direct association between salt intake and obesity independent of energy intake. We analyzed the data from the rolling cross-sectional study–the UK National Diet and Nutrition Survey 2008/2009 to 2011/2012. We included 458 children (52% boys; age, 10 ± 4 years) and 785 adults (47% men; age, 49 ± 17 years) who had complete 24-hour urine collections. Energy intake was calculated from 4-day diary and misreporting was assessed by Goldberg method. The results showed that salt intake as measured by 24-hour urinary sodium was higher in overweight and obese individuals. A 1-g/d increase in salt intake was associated with an increase in the risk of obesity by 28% (odds ratio, 1.28; 95% confidence interval, 1.12–1.45; P = 0.0002) in children and 26% (odds ratio, 1.26; 95% confidence interval, 1.16–1.37; P < 0.0001) in adults, after adjusting for age, sex, ethnic group, household income, physical activity, energy intake, and diet misreporting, and in adults with additional adjustment for education, smoking, and alcohol consumption. Higher salt intake was also significantly related to higher body fat mass in both children (P = 0.001) and adults (P = 0.001) after adjusting for age, sex, ethnic group, and energy intake. These results suggest that salt intake is a potential risk factor for obesity independent of energy intake.